The immune suppressive microenvironment affects efficacy of radio‐immunotherapy in brain metastasis. Issue 5 (23rd March 2021) - Niesel, Katja; Schulz, Michael; Anthes, Julian; Alekseeva, Tijna; Macas, Jadranka; Salamero‐Boix, Anna; Möckl, Aylin; Oberwahrenbrock, Timm; Lolies, Marco; Stein, Stefan; Plate, Karl H; Reiss, Yvonne; et al.
Abstract: The tumor microenvironment in brain metastases is characterized by high myeloid cell content associated with immune suppressive and cancer‐permissive functions. Moreover, brain metastases induce the recruitment of lymphocytes. Despite their presence, T‐cell‐directed therapies fail to elicit effective anti‐tumor immune responses. Here, we seek to evaluate the applicability of radio‐immunotherapy to modulate tumor immunity and overcome inhibitory effects that diminish anti‐cancer activity. Radiotherapy‐induced immune modulation resulted in an increase in cytotoxic T‐cell numbers and prevented the induction of lymphocyte‐mediated immune suppression. Radio‐immunotherapy led to significantly improved tumor control with prolonged median survival in experimental breast‐to‐brain metastasis. However, long‐term efficacy was not observed. Recurrent brain metastases showed accumulation of blood‐borne PD‐L1 + myeloid cells after radio‐immunotherapy indicating the establishment of an immune suppressive environment to counteract re‐activated T‐cell responses. This finding was further supported by transcriptional analyses indicating a crucial role for monocyte‐derived macrophages in mediating immune suppression and regulating T‐cell function. Therefore, selective targeting of immune suppressive functions of myeloid cells is expected to be critical for improved therapeutic efficacy of radio‐immunotherapy in brain metastases. Synopsis: This preclinical study demonstrates the potential of radiotherapy to sensitize breast cancer brain metastasis to checkpoint inhibition. Myeloid cells contribute to immune suppression affecting long‐term survival and therefore represent a target for improved radio‐immunotherapy. Radiotherapy increases CD8 + infiltration into breast cancer brain metastases. Reactivating T cells with immune checkpoint inhibition via anti‐PD‐1 in combination with radiotherapy improves survival and reduces tumor growth. Infiltration of blood borne PD‐L1 + myeloid cells is increased after radio‐immunotherapy and likely suppresses re‐activated anti‐tumor T cell immunity. Abstract : This preclinical study demonstrates the potential of radiotherapy to sensitize breast cancer brain metastasis to checkpoint inhibition. Myeloid cells contribute to immune suppression affecting long‐term survival and therefore represent a target for improved radio‐immunotherapy.